Enhancing Respiratory Function and Cardiovascular Endurance through Intensive Yogic Intervention: A Comprehensive Study - Tarak Nath Pramanik; Aminur Rahaman; Md. Hamidur Rahman; Akash Shukla; Punam Pradhan (OVS LLC, 2024)
Background. Optimal respiratory function and cardiovascular endurance are integral to overall health and athletic performance. Yogic interventions have emerged as potential strategies to enhance physiological and physical parameters. These metrics not only unlock the human body's potential but also play a vital role in increasing sports performance. Objectives. This study aimed to evaluate the effectiveness of a structured yogic regimen in improving respiratory function and cardiovascular endurance in young male adults, shedding light on yoga's role as a complementary approach to physical fitness enhancement. Materials and methods. Forty (N=40) male undergraduate university students (aged 18 to 25 years) were randomly assigned to the experimental (n=20) and control group (n=20). The experimental investigation centered on vital capacity (VC), both positive and negative breath holding times (PBHT and NBHT), peak flow rate (PFR), and cardiovascular endurance (CVE). Using an analytical research approach, a randomized pre-test-post-test-controlled group design was implemented. The experimental group engaged in daily yoga sessions supervised by certified instructors, incorporating various asanas, pranayama techniques, and meditation, while the control group maintained their regular lifestyle. Pre- and post-intervention assessments of respiratory parameters and cardiovascular endurance were conducted using standardized tests. Statistical analyses, including Levene's test for normality, and paired t-tests for intra-group comparisons, were performed using SPSS software (IBM, version 25, Chicago). The experiment lasted for six weeks, with a significance level set at α = 0.05. Results. The paired t-test analyses demonstrated significant improvements in VC t(19) = 4.96, and p <0.000; PBHT t(19) = 6.34, and p <0.000; NBHT t(19) = 4.18, and p <0.001; PFR t(19) = 7.02, and p <0.000; as well as CVE t(19) = 3.96, and p <0.001, within the experimental group. Conversely, no significant changes were observed in the control group. Conclusions. The findings underscore the effectiveness of a six-week yogic intervention in enhancing respiratory function and cardiovascular endurance among young male adults. Integrating yoga into exercise routines may yield substantial benefits for physical fitness improvement.